Wolff's guide to the London Metal Exchange - Rudolf Wolff & Co. (London : Metal Bulletin, 1976)
The object of this book is to commemorate the London Metal Exchange's centenary year of 1977 in a practical and lasting way, by discussing the activities of the metal market and challenges inherent in the market.
Includes bibliographical references.
usc 22/01/2019
Loans
Keywords: Metal trade; Commodity exchanges; Mineral industries; London Metal Exchange; Great Britain